2022
DOI: 10.1111/tbed.14494
|View full text |Cite
|
Sign up to set email alerts
|

A natural outbreak of infectious spleen and kidney necrosis virus threatens wild pearlspot, Etroplus suratensis in Peechi Dam in the Western Ghats biodiversity hotspot, India

Abstract: A large-scale mortality of pearlspot, Etroplus suratensis was reported from Peechi Dam, an artificial tropical lake made for irrigation and drinking water supply in Kerala, India during 2018. This dam is located in the premises of Western Ghats, recognized as one of the biodiversity hotspots of the world. The objective of this study was to identify the aetiological agent of this large-scale mortality of E. suratensis by systematic diagnostic investigation and identification of the pathogen. Virus isolation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
1
0
0
Order By: Relevance
“…The partially characterized ISKNV strain identified in native cichlids in this study was identical to previous strains identified in cultured tilapia and carp in Brazil, suggesting that viral transmission between these species may be possible (Swaminathan et al, 2022). Our findings underscore the importance of implementing proper biosecurity measures in Brazilian aquaculture to both control the impact and spread of endemic diseases as well as to prevent the entry of exotic pathogens.…”
Section: Resultssupporting
confidence: 76%
“…The partially characterized ISKNV strain identified in native cichlids in this study was identical to previous strains identified in cultured tilapia and carp in Brazil, suggesting that viral transmission between these species may be possible (Swaminathan et al, 2022). Our findings underscore the importance of implementing proper biosecurity measures in Brazilian aquaculture to both control the impact and spread of endemic diseases as well as to prevent the entry of exotic pathogens.…”
Section: Resultssupporting
confidence: 76%